POLITICAL COMMUNICATION STRATEGY INDONESIAN NATIONAL ARMY IN HIS ROLE ACCELERATE COVID-19 MANAGEMENT IN INDONESIA - Herman Faisal; Lukman Hakim; Muzahid Akbar Hayat; Andi Syarifauzi; Ahmad Sufian (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
The involvement of the military in the global health crisis has started since the COVID-19 outbreak in Indonesia, starting from the implementation of Large-Scale Social Restrictions to the implementation of the new normal adaptation phase, including the acceleration of vaccination. However, this involvement has its pros and cons. A number of parties regard it as something natural, while others criticize the urgency of involving the military. This study focuses on the political communication strategy of the roles of two defense institutions, namely the Indonesian National Army and the Ministry of Defense in dealing with COVID-19. The methodology used is a qualitative research design. Researchers used role theory, political communication concepts, national defense concepts, and pandemic handling concepts to analyze this study. The results of the study show that the TNI has a role in political PR in changing the good image of its institutions and is closely correlated in providing communication from the government, which is strategically in a number of fields such as health, security, and socio-economics in an effort to tackle COVID-19. The Ministry of Defense also plays a strategic role both internally and externally through collaboration with other ministries, domestic private companies, state-owned enterprises in the defense industry sector, and with other countries in tackling the COVID-19 pandemic.